Social Phenomena Related to Fraudulent General Election Results in Indonesia 2024: Systemic Functional Linguistics Perspective - Eko Sugiarto (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
This research delves into the societal implications of fraudulent general election results in Indonesia, with a specific focus on the 2024 presidential election. Applying Systemic Functional Linguistics, the study examines the language use in elections, the repercussions of fraudulent activities on public trust, and the broader impact on Indonesian society. Through detailed data collection and analysis methods, the study uncovers linguistic patterns in fraudulent clauses, discourse strategies employed, and the manipulation of language to influence public sentiment. By identifying fraudulent clauses in news reports, the research sheds light on the intricate nature of election fraud and its historical context. The findings underscore the significant role of language in shaping perceptions and behaviors within the electoral system, emphasizing the need for valid data in understanding and addressing fraudulent practices. Ultimately, this study contributes to a deeper understanding of election fraud's complexities and its far-reaching consequences on Indonesian society.